Collaboration against infectious diseases in border region between North and South Korea - Jonggeuk Yoon; Yooncheol Choi (선진국방연구, 2023)
This study aims to prepare countermeasures that prevent the spread of infectious diseases including malaria and African Swine Fever (ASF) in regions adjacent to the DMZ and border region between North and South Korea and propose exchanges and collaboration measures between North and South Korea against diseases. For this, we reviewed cases of inter-Korean cooperation promoted by the Korean government or local governments and related studies and examined collaboration and problem factors in health and medicine between North and South Korea. Additionally, rooted by the exchange model for border areas between East and West Germany, we suggest applicable measures in the inter-Korean border areas. We put forward proposals for the continuous and specific development of inter-Korean health and medical cooperation plan on the basis of establishing Committee on Border Areas and Agreement on Health and Medicine by supplementing the limitation of piecemeal approach and support at one-time in North-South Korea relations in the past. Additionally, the current study suggests the need for inter-Korean cooperation at the local government level for joint malaria prevention, and prevention of the spread of livestock infectious diseases.